Effect of sound stress on ovulation, estrus, and conception in beef heifers - G. Heersche Jr.; G. Kiracofe; M. McKee; D.R. Ames (Kansas Agricultural Experiment Station Research Reports, 1974)
Thirty of the 50 heifers used in estrous synchronization studies and that received prostaglandin and Syncro-Mate B to synchronize estrus were subjected to sound stress for 48 hours after prostaglandin was injected. Fifty-nine percent of 29 sound-stressed heifers that showed estrus within 5 days conceived when artificially inseminated compared with 72 percent of 18 nonstressed heifers.
Keywords: Cattlemen& #x27; s Day; 1974; Report of progress (Kansas State University. Agricultural Experiment Station); 210; Beef; Ovulation; Estrus; Conception; Heifers